Applied linguistics: From the circumstances of its emergence to the branching of its development - khain, nmohamed (El Omda in Linguistics and Discourse Analysis, 2019)
Applied Linguistics From the fuzziness of its appearance to the ramifications of evolution In this article, we propose a historical-epistemological approach, whose purpose is to clarify the scientific contexts, and the socio-economic conditions that surrounded the disciplinarization and institutionalization of applied linguistics, taking into account geographical areas in which this discipline has developed in terms, concepts and subjects, as well as the reasons for the divergences of evolution experienced by applied linguistics. at the end of this decade of the third millennium.